2000
DOI: 10.2307/3345395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tone-Quality Conditions on Perception and Performance of Pitch among Selected Wind Instrumentalists

Abstract: The purpose of this study was to assess the effects of changes in tone quality on the perception of pitch and to determine the extent to which the same tone-quality conditions would affect the performance of pitch. The experiment was conducted in two segments: a perception task that involved judgments of paired comparisons of tones, and a performance task that involved tone matching. High school and university wind instrumentalists participated in perception and performance tasks that were similar to provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 21 publications
1
38
1
2
Order By: Relevance
“…Acoustic features such as vibrato (Geringer et al, in press), timbre, pitch, and spectral variability within tones, longterm average spectra, and attack/decay characteristics either alone or in any combination may serve to affect the range of acceptable tuning tolerated by listeners. For example, differences in long-term average spectra between voice, violin, and trumpet performances in the present study (trumpet had the least number and strength of upper harmonics compared to violin and voice) would seem to predict that listeners might hear the trumpet as lower in pitch than violin or voice for equivalent fundamental frequencies (e.g., Worthy, 2000). This provides one possible explanation for listeners' judging the trumpet as most out of tune for the flat deviations.…”
Section: Discussionmentioning
confidence: 60%
“…Acoustic features such as vibrato (Geringer et al, in press), timbre, pitch, and spectral variability within tones, longterm average spectra, and attack/decay characteristics either alone or in any combination may serve to affect the range of acceptable tuning tolerated by listeners. For example, differences in long-term average spectra between voice, violin, and trumpet performances in the present study (trumpet had the least number and strength of upper harmonics compared to violin and voice) would seem to predict that listeners might hear the trumpet as lower in pitch than violin or voice for equivalent fundamental frequencies (e.g., Worthy, 2000). This provides one possible explanation for listeners' judging the trumpet as most out of tune for the flat deviations.…”
Section: Discussionmentioning
confidence: 60%
“…10,11,[13][14][15]21,22 Research has suggested that stimuli with energy concentrated in the higher frequencies are perceived as being sharper than stimuli with energy concentrated in the lower frequencies. 17,19 To more specifically define under what conditions timbre can affect the perception of pitch, Singh and Hirsh 18 generated six types of stimuli with slightly different spectral energy concentrations. Generally, listeners perceived changes in energy concentration as changes in timbre and changes in F 0 as changes in pitch.…”
Section: Introductionmentioning
confidence: 99%
“…The primary acoustic correlate of pitch is fundamental frequency; however, intensity, [3][4][5] duration, 6-8 timbre, [9][10][11][12][13][14][15][16][17][18][19] and perhaps also vibrato 20 have been shown to affect the perception of pitch.…”
Section: Introductionmentioning
confidence: 99%
“…One of the acoustic properties that has been shown to affect perception of pitch across different timbre is spectral composition, i.e., energy distribution in harmonics (Moore et.al, 1992;Patterson, 1990, Singh andHirsh, 1992). Stimuli with greater energy in higher harmonics can shift pitch perception upwards (Worthy, 2000). According to Singh and Hirsh (1992), when the F 0 change is small, less than 2%, spectral centroid change is the primary predictor of perceived pitch change.…”
Section: How Does Timbre Interact With Pitch?mentioning
confidence: 99%
“…However, one study does examine the role of spectral centroid, or energy concentration, in pitch perception. Worthy (2000) investigated the effects of tone quality conditions on pitch perception and performance in 64 high school and college students. Results showed that subjects perceived tones with bright timbre (more energy at higher harmonics) as being sharper and tones with dark timbres (less energy at higher harmonics) as being flatter in pitch.…”
Section: Timbrementioning
confidence: 99%